Summarizing Online Media News Content Using TFIDF Algorithm - Muhammad Didik Rohmad Wahyudi (Kaunia: Integration and Interconnection Islam and Science, 2016)
Online news media has an important role as a source of news and information for the public. In reading the news, the public wants to read the article as short as possible, but can obtain news core. Desire to obtain information quickly can be done by reading the summary of a story. One algorithm that can be used to summarize the content of the news in the online news media are TFIDF algorithm. The contents of the selected message will be read by using the Document Object Model library in the PHP programming language. The results of this research is a summary of the selected online news media are then read by the DOM library to take the news content. Furthermore, the news content will be summarized by using TFIDF algorithms.